Chattering-free discrete-time sliding mode control for integrated missile guidance and control system. (June 2023) - Wang, Xinming; Wu, Di; He, Jingang; Zhang, Jinpeng; Li, Shihua
With the development and validation of flight control devices, electronic equipment is widely used in current flight vehicles, which results in a series of control signals in the discrete-time domain. However, many mature integrated guidance and control schemes are designed in the continuous-time domain, and some results of them may not be preserved in the discrete-time domain especially for the sliding mode control. To address this issue, a chattering-free discrete-time sliding mode control scheme is proposed for the integrated guidance and control systems of missiles. By applying the Euler's discretization method, an approximated discrete-time model with matched and mismatched disturbances is first derived for integrated guidance and control system. Then, the estimates of the disturbances are obtained by using discrete-time generalized proportion integral observers. Integrating the estimated disturbances into the sliding mode variable, a discrete-time sliding mode controller is established by utilizing a modified chattering-free reaching law. The reachability of quasi-sliding mode band, states boundedness, and output convergence performance are analyzed rigorously. Finally, comparative numerical simulations are conducted to verify the effectiveness of the proposed control scheme in the presence of unknown target maneuvers and parameter uncertainties.